Validity of Cooper’s 12-minute run test for estimation of maximum oxygen uptake in male university students - Bandyopadhyay, Amit (Biology of Sport, 2015)
The present study was conducted to validate the applicability of Cooper’s 12-minute run test (CRT) for predicting VO<sub2 max in male university students of Kolkata, India, to bypass the exhaustive and complicated protocol of direct estimation of VO<sub2 max. Eighty-eight sedentary male university students recruited by simple random sampling from the University of Calcutta, Kolkata, were randomly assigned to the study group (N=58) and the confirmatory group (N=30). VO<sub2 max of each participant was determined by the direct procedure and the indirect CRT method. The mean value of predicted VO<sub2 max (PVO<sub2 max) (42.8±4.0 ml · kg -1 · min -1 with a range of 33.7–50.9) showed a significant difference with VO<sub2 max (39.8±4.0 ml · kg -1 · min -1 with a range of 33.5–47.7) in the study group. Limits of agreement between PVO<sub2 max and VO<sub2 max were large enough (0.10 to 5.94 ml · kg -1 · min -1 ) with poor confidence intervals indicating inapplicability of the current protocol of CRT in the studied population. The prediction norm [Y = 21.01X – 11.04 (SEE = 0.193 ml · kg -1 · min -1 )] was computed from the significant correlation (r = 0.93, P<0.001) between distance covered in CRT and VO<sub2 max. Application of this norm in the confirmatory group revealed an insignificant difference between PVO<sub2 max and VO<sub2 max. The modified equation is recommended for application of CRT as a valid method to evaluate the cardiorespiratory fitness in terms of VO<sub2 max in sedentary male Indian youth.